Seigniorage in the EC : The Implications of the EMS and Financial Market Integration. (IMF Working Papers; Working Paper ;, 1989)
The paper measures the effects of the integration of European financial markets and lower inflation in the EMS on the revenue from seigniorage for the EC member countries with particular focus on the high inflation countries. Assuming that by 1992 all EC members participate fully in the EMS and reserve requirements are unified, the revenue from seigniorage will be reduced by about 2 percentage points of GDP in Greece and Portugal and 0.5-0.8 percentage points in Italy and Spain. Two different measures of seigniorage yield similar results regarding the change, but differ regarding the level.